Incidence and risk factors of unplanned retreatment following dental general anesthesia in children with severe early childhood caries - Li, Jin-yi; He, Shu-yang; Wang, Pan-xi; Dai, Shan-shan; Zhang, Shu-qi; Li, Zheng-yang; Guo, Qing-yu; Liu, Fei (Frontiers in Pediatrics, 2023)
Objective: We aimed to retrospectively describe the unplanned retreatment of dental general anesthesia (DGA) in children with severe early childhood caries (S-ECC) and explore potential factors that may influence the outcome of DGA treatment. Methods: Medical records of children with S-ECC who received DGA treatment were screened, and necessary data were extracted. The Kaplan‒Meier method and Cox proportional hazards model were used to estimate the DGA survival rate and explore the potential factors affecting the success rate of DGA treatment. Results: Medical records of 852 children were included; 509 (59.7%) children with 1212 (10.7%) teeth underwent unplanned retreatment. Restoration failure (30.12%) and new caries (29.46%) accounted for the most significant proportion of all failures. The median survival times were 510 and 1911 days at the child and tooth levels, respectively. Unplanned retreatment risk was associated with the age of S-ECC children, frequency of follow-up and fluoride application (hazard ratio=0.97, 0.78, 0.69, P<0.001). Conclusion: The treatment outcome of DGA administered to children with S-ECC was satisfactory at tooth level from the perspective of the incidence of unplanned retreatment. Restoration failure was the main reason for high unplanned retreatment rate. Strategies for a better outcome of DGA include improving professional knowledge and skills of pediatric dentists, and enhancing compliance of parents/patients. Health education and regular topical fluoride application may improve the success rate of DGA treatment.